Supraspecific taxonomy of Palaearctic Platycleidini with unarmed prosternum: a morphological approach (Orthoptera: Tettigoniidae, Tettigoniinae) - Massa, Bruno; Fontana, Paolo (Zootaxa, 2011)
Authors analysed 33 supraspecific taxa of Palaearctic Platycleidini with unarmed prosternum, most of them hitherto considered genera or subgenera of Platycleis and Metrioptera. For each of them they give a short description of the characters revealing the correct classification of males and females. Then, they propose a more consistent classification, when both males and females of a supraspecific taxon are clearly distinct, they should be elevated to distinct genera. On the whole, they propose to classify Palaearctic taxa into 32 genera, for which they propose a key based on the characters used in this paper and illustrated by 140 photographs. Additionally, they describe the following new genera: Sardoplatycleis for Platycleis galvagnii from Sardinia, Amedegnatiana for Parnassiana vicheti from Mediterranean France; and the following new species: Platycleis buzzettii from Iran and Squamiana bressani from Uzbekistan. For each genus they list all the species known, pointing out also those which, for scarcity of specimens, have been tentatively classified within that genus and that probably should be better assigned to another one. Further, they synonymise Incertana with Decorana, define the actual taxonomical status of the group Roeseliana roeselii, R. fedtschenkoi, R. azami and R. brunneri, reinstate Tessellana carinata from Balkan peninsula, establish that T. nigrosignata is restricted only to S Italy, while in Balkan peninsula its related T. orina occurs.